Weight Behavioral Changed among College Student In Indonesia as Impact of Covid-19 Pandemic: A Structural Equation Model - Dewanti, Lintang Purwara; Sitoayu, Laras; Melani, Vitria; Khairani, Nurul (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: One of the community groups affected by the Covid-19 pandemic is college students. The pandemic has changed the learning system that requires college students to study from home. In addition, it changes college student life habits, including physical activity, diet, body composition, stress, changes in body weight, and others. Objective: Aim to model the impact of the pandemic on weight changes in college students in Indonesia. Method: this study was conducted on 1185 college students for 35 days with a cross-sectional design. The research design used a cross-sectional study design. Analysis of the data used is SEM with LISREL. Result: The results showed a causal relationship between the latent variables of significant lifestyle factors on consumption factors and important consumption factors on changes in body weight in a positive direction. Structural model of the determinants of weight change = 0.05 consumption + 1.03 lifestyle. Conclusion: Lifestyle and consumption factors affect changes in body weight during the Covid 19 Pandemic in college students. Recommendation: There needs to be more attention to public health after the Covid-19 Pandemic hit, especially regarding consumption patterns and stress. People must be able to adjust to new normal conditions so as not to vent their stress by consuming lots of snacks or foods high in fat and sugar